2022
DOI: 10.3390/vetsci9100546
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Perioperative Antimicrobial and Anti-Inflammatory Drugs Regimens for Colic Surgery in Horses: A Single Center Report

Abstract: Reducing postoperative incisional infection is the main reason to administer postoperative antimicrobials (AMD) after emergency laparotomy in horses, while reducing inflammation and providing analgesia are the reasons to administer anti-inflammatory drugs (AID). The basis for postoperative AMD and AID administration is empirical and only recently has been questioned. Empirical approaches can be changed, and these changes, along with the description of their outcomes, can help produce appropriate stewardship. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In another study, horses having colic surgery receiving a single dose of penicillin and gentamicin pre-operatively had an infection rate that was no different to horses receiving 5 days of antimicrobials, albeit the infection rate in the one-dose group was 23% and the 5-day group 5% (Stöckle et al, 2021). Gandini et al (2022) proportion of patients with SAP discontinued within 24 h of surgery (Bratzler & Houck, 2005;Fernández et al, 2001).…”
Section: Ba S I C S Of Sapmentioning
confidence: 96%
See 1 more Smart Citation
“…In another study, horses having colic surgery receiving a single dose of penicillin and gentamicin pre-operatively had an infection rate that was no different to horses receiving 5 days of antimicrobials, albeit the infection rate in the one-dose group was 23% and the 5-day group 5% (Stöckle et al, 2021). Gandini et al (2022) proportion of patients with SAP discontinued within 24 h of surgery (Bratzler & Houck, 2005;Fernández et al, 2001).…”
Section: Ba S I C S Of Sapmentioning
confidence: 96%
“…In another study, horses having colic surgery receiving a single dose of penicillin and gentamicin pre‐operatively had an infection rate that was no different to horses receiving 5 days of antimicrobials, albeit the infection rate in the one‐dose group was 23% and the 5‐day group 5% (Stöckle et al, 2021). Gandini et al (2022) similarly reported that horses not receiving post‐operative antimicrobials following colic surgery did not have a higher incidence of complications compared to horses receiving post‐operative antimicrobials. The author currently uses SAP (potassium penicillin and gentamicin) for 24 h (a single dose of gentamicin before surgery [8.8 mg/kg i.v.]…”
Section: Basics Of Sapmentioning
confidence: 99%
“…Recommendations for antimicrobial duration in veterinary practice further support administration for the shortest effective duration to reduce risk of development of resistant pathogens (Gandini et al, 2022;Hansen et al, 2014); therefore, local surgical and topical techniques to address biofilm formation will be emphasised to minimise unnecessary systemic antimicrobial administration. Early recognition of the presence of biofilms in nonhealing wounds and targeted treatments are key to the successful management of biofilms in equine practice .…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this review is to summarise the current literature describing problems caused by bacterial biofilms in wounds, clinical indications that biofilms are involved, laboratory testing to improve biofilm detection and biofilm‐based wound‐care (BBWC) strategies to provide clinicians in general and referral practice with practical guidelines for case management where biofilms are suspected. Recommendations for antimicrobial duration in veterinary practice further support administration for the shortest effective duration to reduce risk of development of resistant pathogens (Gandini et al., 2022; Hansen et al., 2014); therefore, local surgical and topical techniques to address biofilm formation will be emphasised to minimise unnecessary systemic antimicrobial administration. Early recognition of the presence of biofilms in nonhealing wounds and targeted treatments are key to the successful management of biofilms in equine practice (Pezzanite et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence has called into question appropriate duration of antimicrobial administration following exploratory celiotomy in horses [6,9]. General guidelines in veterinary medicine support the concept that antimicrobials should be administered for the shortest effective duration to minimize development of resistant pathogens [10,11]. In humans, antimicrobial use beyond 24 h postoperatively has not been shown to reduce the risk of surgical site infection for clean-contaminated or dirty procedures [12].…”
Section: Introductionmentioning
confidence: 99%